The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.20471/acc.2019.58.s1.08
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthetics and Steroids: Contraindications and Complications - Clinical Update

Abstract: SUMMARYThe objective of this clinical update, based on recently published literature, was to discuss incidence and characteristics of the most relevant clinical adverse effects associated with local anesthetic and steroid use in regional anesthesia and treatment of acute or chronic pain. A comprehensive review of the English-language medical literature search utilizing PubMed, Ovid Medline® and Google Scholar from 2015 to 2018 was performed. This narrative review provides anesthesia practitioners with updated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
0
14
0
4
Order By: Relevance
“…), joint infection (septic arthritis, cellulitis, osteomyelitis, etc. ), fracture, osteoporosis, coagulopathy, skin defect, hypersensitivity to the steroid, uncontrolled hyperglycemia; also, some complications such as bleeding, bruising, swelling, infection, post-injection pain (steroid flare), face flushing, skin depigmentation, cutaneous atrophy can occur [23].…”
Section: Discussionmentioning
confidence: 99%
“…), joint infection (septic arthritis, cellulitis, osteomyelitis, etc. ), fracture, osteoporosis, coagulopathy, skin defect, hypersensitivity to the steroid, uncontrolled hyperglycemia; also, some complications such as bleeding, bruising, swelling, infection, post-injection pain (steroid flare), face flushing, skin depigmentation, cutaneous atrophy can occur [23].…”
Section: Discussionmentioning
confidence: 99%
“…This combination was preferred, as it was previously reported to provide an effective and long-lasting pain relief. [ 23 ] Due to the anti-inflammatory effects of corticosteroids, the VAS scores at two and three months after the SCN block were lower than the VAS scores before the SCN block.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of dexamethasone and levobupivacaine improves postoperative analgesia and extends duration of the block. A meta-analysis of 14 studies showed that the combination of dexamethasone and levobupivacaine for brachial plexus block improved postoperative analgesia without increasing the incidence of complications ( 6 ). To the best of our knowledge, ESP block was, to this instance, mostly used in postoperative analgesia concomitantly with paracetamol following laparoscopic interventions and thoracic, abdominal, urologic and orthopedic surgical procedures.…”
Section: Discussionmentioning
confidence: 99%